Online learning during COVID-19 pandemic: Problems faced by midwifery students of STIK Bina Husada Palembang and suggestions to enhance effectiveness - Agus Wahyudi (Relawan Jurnal Indonesia, 2021)
COVID-19 or widely known as Corona Virus Disease 2019 influences the teaching and learning process in the world. Due to prevent the spread of the virus, the Ministry of Education and Culture ask the teachers to teach the students using online learning. Therefore, the aim of this study is to find out the problems faced by the midwifery students of STIK Bina Husada Palembang and suggestions to enhance effectiveness of online learning. The descriptive research was applied. There were 35 students involved in this research, namely Midwifery students of STIK Bina Husada Palembang in the academic year of 2020/2021. The data were collected using questionnaire and were analyzed qualitatively with interactive model, covering data collection, data reduction, presentation, and conclusion. Having implemented the online learning during Covid-19 Pandemic, the students, parents, and the teachers got problems of online learning. The problems can be overcome by implementing some suggestions mentioned in this research.